Sharīʿa and Custom in Libyan Tribal Society : An Annotated Translation of Decisions from the Sharīʿa Courts of Adjābiya and Kufra - Layish, Aharon, (Brill Book Archive Part 1, ISBN: 9789004472495., 2005)
This volume presents annotated English translations of 72 court decisions handed down by the the Sharīʿa Courts of Adjābiya and Kufra roughly during the period 1930-1970; the original texts (facsimiles and edited documents) appeared in A.Layish, Legal Documents on Libyan Tribal Society in Process of Sedentarization (Wiesbaden, 1998). The documents address personal status, succession, homicide and bodily injury, property, obligation, and attest to the interaction between the sharīʿa representing normative Islam, and tribal customary law, representing social reality in Cyrenaica during the aforementioned period. They also exemplify the qadi 's role of bringing a Bedouin society within the orbit of normative Islam. A.Borg's essay Orality, Languages, and Culture in Arabic Juridical Discourse addresses cultural aspects of orality on the language of these documents. The study is intended for Orientalists, Islamologists, legal and social historians, social scientists, and lawyers interested in Islamic and comparative law.